(untitled) (International Journal of Food and Nutritional Sciences, 2013)
Lonar crater and its surrounding area is an important Geomorphic and Geological structure. It is the largest meteoritic crater in basaltic rock of India. It is one of the unique meteoritic features of the world. Therefore it is known as a natural wonder of the world. It is located at Buldhana district of Maharashtra, India. (19o 58’50’’ N lat. and76o 30’50’’E long.) In the present investigation simple, bowl-shaped, nearly circularly impact crater found near the 4.3 k.m from the Lonar crater. This relatively small crater is of particular interest because of its unique morphological and hydrological properties, which make it a valid analogue for similar craters. In the field observation glassy objects of impact origin have been found in the the crater for its unique ecosystem. a small crater 100 m. in dia-meter depression about 700m away from the rim of the Lonar crater, and suggested that it may be a recent field work